Exploring Metabolites Of Green Algae Caulerpa Spp. To Discover Putative Inhibitors Of Dpp-4, A New Antidiabetic Target Protein: Molecular Docking Compounds from Marine Green Algae - Balansa, Walter (Jurnal Ilmiah Platax, 2023)
Diabetes mellitus (DM) remains a serious global health threat, claiming a million lives every year and affecting nearly 9% of the adult population who suffer from this impaired insulin sensitivity disease. The Dipeptidyl peptidase-4 (DPP-4) enzyme has recently attracted attention because of its crucial role in insulin signaling, making this enzyme an interesting and emerging target for antidiabetic drug discovery. This study aimed to explore reported metabolites from marine algae of the genus Caulerpa as DPP-4 inhibitors through computational studies using CB-dock 2, Protein-Ligand Interaction Profiler, SwissAdme, and pkCMS. Molecular docking allowed the identification of 7 hit compounds with strong binding affinities (8.4 kcal to 9.3 kcal/mol) against DPP-4 target enzyme PDB ID: 3G4I. Four hits showed stronger binding affinity than two DPP-4 specific inhibitors and FDA-approved antidiabetic drugs, sitagliptin (8.4 kcal/mol) and linagliptin (9.0 kcal/mol). Following a molecular modification of the hit compounds using a bioisosterism-like approach and ADMET evaluation with pkCMS, three putative DPP-4 inhibitors were identified. They showed either stronger binding affinities or better ADMET profiles than sitagliptin and linagliptin, suggesting their promising potential as DPP-4 inhibitors. However, further optimized bioisoterism, in silico and in vivo studies, and clinical-based trials are required to confirm their antidiabetic activity. Keywords: Antidiabetic, Caulerpa racemosa, caulerpin, DPP-4